2019
DOI: 10.1111/jocn.14996
|View full text |Cite
|
Sign up to set email alerts
|

On the difficulty of finding one’s place: A qualitative study of new nurses’ processes of growth in the workplace

Abstract: Aims and objective To explore new nurses’ processes of growth in the workplace in order to understand the challenges they face. Background Quantitative and qualitative research to date has not adequately explored the complex ways in which initial work experiences may shape new nurses’ very high quit rate and, consequently, impact the long‐term nursing shortage in Taiwan. Design/Methods We conducted in‐depth interviews with new nurses to explore their professional development, including the challenges they face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
5
7
0
Order By: Relevance
“…The participants experienced psychological conflicts arising from stress and tension due to their inexperience and confusion, which was caused by the gap between the theories they learned in school and in-hospital clinical practice. Our findings were consistent with previous studies showing that new nurses experience disillusionment and shock as they face role conflicts because of the gap between the expectations and realities of their work [20]. In other countries, a substantial orientation period is considered important for facilitating new nurses' smooth adaptation to their work environment [21,22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The participants experienced psychological conflicts arising from stress and tension due to their inexperience and confusion, which was caused by the gap between the theories they learned in school and in-hospital clinical practice. Our findings were consistent with previous studies showing that new nurses experience disillusionment and shock as they face role conflicts because of the gap between the expectations and realities of their work [20]. In other countries, a substantial orientation period is considered important for facilitating new nurses' smooth adaptation to their work environment [21,22].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in line with the results of previous studies that suggest that self-confidence and work satisfaction decrease in new nurses [24,25] because of frequent work-related mistakes [26,27]. Moreover, a negative relationship with senior nurses, upon whom they are reliant, imparts a sense of betrayal, leading to feelings of hatred and sadness [20]. Therefore, it is understandable that Cheng et al [4] reported that new nurses with three to six months of work experience have a high intention of changing careers.…”
Section: Discussionsupporting
confidence: 91%
“…Better evaluation of transition will contribute to better support for the new nurses and promote their professional confidence and competence (Hussein et al., 2017). However, the existing tools are neither sufficient nor convenient when evaluating the transition process (Cline et al., 2017; Ke & Stocker, 2019). The Transition Status Scale for Newly Graduated Nurses is newly developed to enrich and facilitate the accurate assessment of the transition status.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare settings face challenges regarding recruitment and retention of nurses from an international perspective (Ahlstedt et al, 2019;Cummings et al, 2010;Ke & Stocker, 2019;Rudman et al, 2014), and residency programmes have emerged as an intervention to support newly graduated nurses (henceforth referred to as nurses) in their transition to professional nurses (Beecroft et al, 2001;Olson-Sitki et al, 2012). However, oriented and supportive structures have a wide variation for nurses entering healthcare organisations (Kovner et al, 2007).…”
Section: Introductionmentioning
confidence: 99%